Load Distribution on the Neck of Malvi Breed of Bullocks at Different Draft Loads - Singh, R C; Singh, C D; Singh, V V; Dubey, U C (Journal of Agricultural Engineering, 2007)
The load distribution on neck of Malvi breed of bullocks was studied with local/improved Nagpuri yoke and Allahabad three-padded collar double animal harness at different draft loads. The miniature button type load cells (capacity 0 - 500 N) were mounted on three planes (left, middle and right) of the contact surface of the yoke/harness with the neck of the animals. The CIAE animal-loading car was used to apply the different draft loads to the animals. The study showed that the Nagpuri yoke was more efficient and comfortable to pull the draft loads by a pair of bullocks as the mean vertical loads on the contact surface of the Nagpuri yoke with the neck of bullocks were significantly less as compared to that of the local yoke. Similarly, the mean vertical loads were evenly distributed on the top pad of Allahabad three-padded collar double animal harness for the draft loads of 800, 1000 and 1200 N. The mean vertical loads were very high at the contact points on left and right side pads of Allahabad three-padded collar harness with the neck of bullocks as compared to others points. Hence, design modification is required on left and right side pads of Allahabad three-padded collar harness for even distribution of vertical loads on the neck of bullocks to enhance the higher work output.